PENINGKATAN PERILAKU IBU DENGAN ANAK STUNTING USIA 0-24 BULAN MELALUI PENDAMPINGAN OLEH KADER KESEHATAN MENUJU KAMPUNG KB BEBAS STUNTING - Demsa Simbolon; Emy Yuliantini; Yusmidiarti; Bringwatty Batbual; Ina Debora Ratu Ludji; Eliana (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
Stunting is a nutritional health problem that shows the failure to thrive in children under five due to chronic malnutrition. Liner growth failure in stunting is associated with increased morbidity and mortality. The service activities aim to foster and empower groups of toddlers as nutritional companions to increase mothers' knowledge, attitudes, and actions of mothers with stunting children aged 0-24 months to prevent and control stunting. The target audience is 80 mothers with stunted children aged 0-24 months, consisting of 40 mothers in the Kampung KB area of ​​ working area Padang Serai Health Center, Bengkulu City, and 40 mothers in the Kampung KB  of the working area of ​​Pasir Panjang Health Center, Kupang City. Community service results showed a significant increase in the knowledge, attitudes, and action of cadres under five in preventing stunting before and after the training. The cadres formed are fostered and involved in community empowerment activities in the working area of ​​the Public health center. And there is an increase in the knowledge, attitudes, and actions of mothers under five in preventing stunting. Follow-up is needed for Cadres who are responsible for continuing activities in the target group until the age of 5 years with guidance by health workers by making regular mentoring schedules until the child is five years old. --- Stunting masih menjadi masalah kesehatan prioritas untuk dicegah dan ditanggulang karena penyebab dan dampaknya yang kompleks. Kegiatan pengabdian kepada masyarakat menerapkan intervensi satu rumah satu meteran deteksi risiko stunting (MDRS). Tujuan kegiatan pengabdian untuk membina dan memberdayakan kelompok kader balita sebagai pendamping gizi untuk meningkatkan pengetahuan, sikap dan tindakan ibu balita stunting usia 0-24 bulan dalam pencegahan dan penanggulangan stunting. Kalayak sasaran adalah ibu balita stunting usia 0-24 bulan sebanyak 80 ibu yang terdiri dari 40 ibu baduta di Kampung KB Padang Serai Kota Bengkulu dan 40 ibu baduta di Kampung KB Pasir Panjang Kota Kupang. Hasil Pengabdian kepada masyarakat menunjukkan terjadi peningkatan signifikan pengetahuan dan sikap kader dalam pencegahan stunting sebelum dan sesudah pelatihan. Kader yang terbentuk dibina dan dilibatkan dalam kegiatan-kegiatan pemberdayaan masyarakat di wilayah kerja puskesmas. Terjadi peningkatan yang signifikan pengetahuan, sikap, serta tindakan Ibu baduta dalam pencegahan stunting. Perlu tindak lanjut untuk kader bertanggung jawab melanjutkan kegiatan pada kelompok sasaran sampai berusia 5 tahun dengan pembinaan oleh tenaga kesehatan  dengan  membuat jadwal pendampingan secara berkala sampai anak berusia 5 tahun.